OPTIMALISASI POTENSI DAN EFEKTIVITAS PENERIMAAN RETRIBUSI PASAR DI PASAR WAGE PURWOKERTO KABUPATEN DATI II BANYUMAS - suhardoyo suhardoyo (Widya Cipta - Jurnal Sekretari dan Manajemen, 2018)
ABSTRACT To maximize regional autonomy and promote development, as well as to reduce donations from the central government, local governments must increase local revenue (PAD). One of them is by increasing the revenue from the market retribution.Sehingga if managed optimally in pungutannyanya it will be able to contribute large enough for the opinion of the Original Region. To achieve optimal results, it is necessary to collect efficiently and effectively by the officers. For this reason we conduct research related to the optimization of retribution revenue in terms of efficiency and effectiveness of retribution pengutan in Purwokerto wage market. The result of research indicate that the acceptance of Levy in Purwokerto wage market still not optimally show the acceptance equal to Rp 180,565,500,00 whereas according to the calculation with linear programming to achieve optimal result show the acceptance equal to Rp 196.662.000,00 with combination of merchant type average per day stalls 73 people, traders losing 389 people and traders lesehan amounted to 350 people. So there is a difference of retribution income per year Rp 16.096.500,00. While the withdrawal of retribution levies Kiosk traders and merchants lesehan been implemented Effectively because based on the calculation of effectiveness has value = 1, While the execution of retribution market retribution Los merchants show results that have not been effective with a value of 0.86 <1 Keywords: Potency and Effectiveness, Market retribution